Corrosion modeling for condition assessment of offshore jacket Leg for life extension - POULINO, MBIKOYESU MOSES (IRC, 2016)
As structures age, their structural reliability to sustain operations becomes a crucial issue, especially in the oil and gas industry. In this study, corrosion a critical issue to their performance has been studied. The main parameters of size and location of localized corrosion attack has been extensively analysed with the aid of Finite Element Analysis (FEA) software, ANSYS workbench. The corrosion is represented as an elliptical cut on the surface of the leg. The study focuses on the outcome obtained for Von-Mises stress and deformation on application of the pushover analysis on varying loads. Von-Mises stress basically predicts the yielding of the material stress on application of environmental loadings; meanwhile the structures deformation defines the change in shape of the structure. The results obtained indicates that corrosion causes higher stress at the areas closer to the joint supports as compared to the mid of the section